Iván Molina Jiménez. A provincial printer. The Sibaja workshop in Alajuela, Costa Rica, 1867-1969. Alajuela MHCJS, 2002 - Viales, Ronny (Revista de historia., 2002)
This work is divided into two large parts. The first represents, in my opinion, an excellent interpretative synthesis, which has only been possible due to Ivan Molina’s prolific research over the last decade. The second is a collection that reveals the author’s unselfish attitude, given that, in many cases, the historian prefers to treasure the primary sources he compiles, rather than share them with his colleagues and apprentices, an attitude that has never been the tonic in the work of the Molina researcher.